Will there be large or small gifts to PDM3 attendees and EJTM authors in March and June 2023? - Ugo Carraro; Rosanna Piccirillo; Stefano Masiero; Jannis Papathanasiou; Marcus Coplin (European Journal of Translational Myology, 2022)
The fall of 2022 approaches with the need to finalize our plans for next year. This is urgent for the 2023 Meeting of the Padua Days of Muscle and Mobility Medicine, (PDM3) to be held March 29 to April 1, 2023 at the Hotel Petrarca in the Thermae of Euganean Hills (Padua), Italy, but there are also news related to the inclusion of the European Journal of Translational Myology (EJTM) in the Web of Science: Emerging Sources Citation Index – Clarivate (ESCI) database. A preliminary PDM3 flyer is almost ready with session program, organzers and keynote speakers. Some are the traditional organizers of the PDM3 sessions dedicated to molecular and cellular myology, but there will also be interesting new entries, including those of Rehabilitation Sessions. No doubt that PDM3 2023 will be a great gift for all Participants, as is the tradition of PDM3. The other big news scheduled for June 2023 is the Impact Factor 2022 that Clarivate will release next year. It could be a big or small gift. As Authors who publish in other Magazines, but even more as Referees we could contribute in the next months of 2022 to make a small gift from Clarivate bigger. In any case, it will be a great gift that has been awaited for many years for one of us, who is approaching 80 years of age next February 2023.